The kaleidoscopic midwife: A conceptual metaphor illustrating first-time mothers' perspectives of a good midwife during childbirth. A grounded theory study - Borrelli, Sara E.; Spiby, Helen; Walsh, Denis (Elsevier, 2016)
Background: The literature review reveals general information about a good midwife from a range of perspectives and what childbearing women generally value in a midwife, but there is a lack of information around mothers’ perspectives of what makes a good midwife specifically during labour and birth, and even less in the context of different places of birth. Aim: To conceptualise first-time mothers’ expectations and experiences of a good midwife during childbirth in the context of different birthplaces. Design: Qualitative Straussian grounded theory methodology. Setting: Three National Health Service Trusts in England providing maternity care that offered women the possibility of giving birth in different settings (home, freestanding midwifery unit and obstetric unit). Participants: Fourteen first-time mothers in good general health with a straightforward singleton pregnancy anticipating a normal birth. Methods: Ethical approval was gained. Data were collected through two semi-structured interviews for each participant (before and after birth). Data analysis included the processes of coding and conceptualising data, with constant comparison between data, literature and memos. Findings: The model named ‘The kaleidoscopic midwife: a conceptual metaphor illustrating first-time mothers’ perspectives of a good midwife during childbirth’ was developed. The model is dynamic and woman-centred, and is operationalised as the midwife adapts to each woman's individual needs in the context of each specific labour. Four pillars of intrapartum care were identified for a good midwife in the labour continuum: promoting individuality; supporting embodied limbo; helping to go with the flow; providing information and guidance. The metaphor of a kaleidoscopic figure is used to describe a midwife who is ‘multi-coloured’ and ever changing in the light of the woman's individual needs, expectations and labour journey, in order to create an environment that enables her to move forward despite the uncertainty and the expectations-experiences gap. The following elements are harmonised by the kaleidoscopic midwife: relationship-mediated being; knowledgeable doing; physical presence; immediately available presence. Conclusion: The model presented has relevance to contemporary debates about quality of care and place of birth and can be used by midwives to pursue excellence in caring for labouring mothers. Independently from the place of birth, when the woman is cared for by a midwife demonstrating the above characteristics, she is likely to have an optimum experience of birth. Future research is necessary to tease out individual components of the model in a variety of practice settings.